Death, Dying, Funeral And Mourning Rıtuals in Alevi Communıties - Aktaş, Ali (Journal of Alevism-Bektashism Studies, 2017)
Every communities in the world has a belief system and they have maintained their religional funeral rituals based on their beliefs. Alevi communities have also maintained their funeral rituals based on their belief system. Perception of death, reacting to death, understanding of death, and funeral ceremonies in Alevi communities can be changed according to zone of occupation. Thus, there are little differences in Alevi communities in this rituals. These differences depend on their geographic coordinations. There aren’t any limitation time for funeral rituals and certain religional rules for funeral rituals in Alevi communities and these elements has resulted from aforesaid differences.There are some idioms in Alevi communities like “Coalesced into Allah”, “to merge with the Almighty ”, “We came from Allah and return to Allah.” Because of these idioms, when somebody dies nobody say “dead” for him. Everybody will say “He returned to God.” or “He changed his skin-dress.” These words and idioms means not only “death, to be gone, seperate” but also “reach”, “to merge to Maker”. Because of these reason these rituals named “The Way for Merge to Almighty” instead of “Funeral Ritual.”In this research understanding death and dying in Alevi communities, patients and visitations rules to them, responsibilities of society to deadly ill person, The Way for Merge to Almighty Rituals, process for society after dying (preparing shroud, bathing the deceased, shrouding, ask for deceased’s blessing, performing the salaat without sadjah, carrying the funeral, carrying out feet foremost, condolencing, rituals and traditions after dying for Alevi society) has been discussed. These topics has been discussed in terms of oral Alevi traditions, gulbanks, prays and rituals.
Keywords: Alevis; Death and Dying; Funeral; Mourning; Gulbank (Pray); Rituals